2009
DOI: 10.1016/j.yofte.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of birefringence dispersion on a distributed stress sensor using birefringent optical fiber

Abstract: Copies of full items can be used for personal research or study, educational, or not-for-profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For both types of fibers, a maximum sensitivity can be achieved when the force is applied at 90 in relation to the fiber slow axis. The experiments have also confirmed that the sensitivity of these specialized pressure sensors is independent of the fiber length and of the axial location of the force along the fiber length compared to the other sensors [11]. This makes the sensors more suitable for distributed force measurement.…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…For both types of fibers, a maximum sensitivity can be achieved when the force is applied at 90 in relation to the fiber slow axis. The experiments have also confirmed that the sensitivity of these specialized pressure sensors is independent of the fiber length and of the axial location of the force along the fiber length compared to the other sensors [11]. This makes the sensors more suitable for distributed force measurement.…”
Section: Methodsmentioning
confidence: 53%
“…This paper has been focused on the discussions of the phase-based pressure sensor technique. There have been some other reports showing intensity-based technique, such as [11], which reported that the lateral pressure sensitivity of PM fibers is dependent on the magnitude and angle of external transverse forces theoretically and supported by one directional measurement data. Regarding the cross sensitivity to the other parameters, such as temperature, [12] has shown that such a sensor is not dependent on temperature variation and this conclusion was further confirmed by Wierza et al [13] after the transverse force was applied, respectively, in the direction of fast and slow axis of a two-hole fiber.…”
Section: Introductionmentioning
confidence: 75%
“…It has been reported that the lateral pressure sensitivity of PM fibres is dependent on magnitude and angle of external transverse forces with reference to fast or slow axis of the fibre [9], which was further confirmed by Wierza et al after the transverse force was applied respectively in the direction of fast and slow axis of a two-hole fibre [10]. This work, however, is aimed to undertake a more thorough investigation to evaluate the lateral pressure sensitivity of both sidehole(s) fibres, shown in Figure 1, as a function of the angle and magnitude of the external transverse force applied and thus to cross-compare the results obtained from these two different structured side-hole fibres.…”
Section: Introductionmentioning
confidence: 99%
“…A novel transverse strain sensor based on the Solc filter is reported in [4] which also uses birefringent fibres. It has been reported that the polarisation mode dispersion (PMD) influences the performance of sensors using Hi-Bi fibres [5,6]. This Letter aims to reveal the impact of PMD on the sensitivity of the transverse strain sensor based on the Solc filter.…”
mentioning
confidence: 97%